AXONAL AGRANULAR RETICULUM AND SYNAPTIC VESICLES IN CULTURED EMBRYONIC CHICK SYMPATHETIC NEURONS - Teichberg, Saul (The Rockefeller University Press, 1973)
Cultured chick embryonic sympathetic neurons contain an extensive axonal network of sacs and tubules of agranular reticulum. The reticulum is also seen branching into networks in axon terminals and varicosities. The axonal reticulum and perikaryal endoplasmic reticulum resemble one another in their content of cytochemically demonstrable enzyme activities (G6Pase and IDPase) and in their characteristic membrane thicknesses (narrower than plasma membrane or some Golgi membranes). From the reticulum, both along the axon and at terminals, there appear to form dense-cored vesicles ranging in size from 400 to 1,000 Å in diameter. These vesicles behave pharmacologically and cytochemically like the classes of large and small catecholamine storage vesicles found in several adrenergic systems; for example, they can accumulate exogenous 5-hydroxydopamine. In addition, dense-cored vesicles at the larger (1,000 Å) end of the size spectrum appear to arise within perikaryal membrane systems associated with the Golgi apparatus; this is true also of very large (800–3,500 Å) dense-cored vesicles found in some perikarya.